Maimonides’ Menstrual Reform in Egypt - Krakowski, Eve (The Jewish quarterly review, 2020)
In the spring of 1176, Maimonides ordered Jewish women throughout Egypt to observe rabbinic menstrual purity laws or risk major financial loss: the dowers their husbands had promised them at marriage. Scholars have understood this decree mainly in context of Karaite-Rabbanite relations, or as inspired by a mass refusal among women in twelfth-century Egypt to perform rabbinic immersion. Both frameworks were first suggested by Maimonides himself, but both are misleading. In this essay I argue that the decree instead responded to an otherwise unknown aspect of medieval “common Judaism”: a quasi-biblical and nonrabbinic—but not markedly Karaite—menstrual purity regime that had prevailed among Jews throughout the medieval Middle East for centuries. After reconstructing these biblicizing menstrual practices, the essay examines the novel administrative tools that Maimonides, breaking from the long-established political norms of Jewish communal leadership in Egypt, deployed to end them, and the ways in which Jewish husbands and wives deployed these tools in turn in the decades afterward—not always as Maimonides had intended them to. The story of this reform offers an exceptional window onto Maimonides’ great project of rabbinic normativization as it played out not on the pages of the Mishneh Torah but on the ground in Egypt in his own day—its radical political character as well as its complex social effects and social limits, especially as these affected women within the equally but differently gendered spheres of the household and the rabbinic courtroom.